(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2023)
The development of electronic systems like Field-Programmable Gate Array (FPGA) made them available for mass commercial use. This created conditions for the development and application of software and technical tools implemented on FPGA algorithms for fast processing of digital signals. Such solutions, in turn, opened up new opportunities for the spread of multi-frequency eddy current systems (МFЕС) for non-destructive testing (NDT) in the form of systems for simultaneous processing of digital signals of different frequencies, which allows MFEC to effectively compete with pulsed eddy current systems (PEC). This work presents a new algorithm for accurate digital measurement of the MFEC amplitude and phase of harmonic components of polyharmonic signals, which is implemented in hardware and software on FPGA. The measurement of the amplitude and phase of harmonic components is based on the method of orthogonal processing of digital signals, to increase the accuracy of which the necessity of fulfilling the condition of multiplicity of the sampling sequence to the size of the digital signal period has been proved. Compliance with this condition is achieved by adjusting the length of the sampling sequence, which in the proposed algorithm is performed before orthogonal processing. The influence of inaccuracy in setting the length of the sampling sequence on the size of measurement errors when determining the amplitude and phase of the harmonic components of the signal is simulated. As a result of the simulation, it was established that when the multiplicity condition is met, the measurement error significantly decreases, which indicates the high efficiency of our algorithm. The achieved accuracy of measuring the amplitude of harmonic components and the phase of polyharmonic signals due to the given hardware and software implementation of the algorithm makes it possible to create inexpensive, compact, scalable automated digital systems, the measurement data of which can be used both to determine the individual characteristics of the object and to reconstruct three-dimensional images, i.e. in tomographic systems.